063. Characteristics and Predisposing Factors of Bile Duct Injury in Hasan Sadikin General Hospital - Audina, Florence; Nugraha, Prapanca; Sulthana, Bambang Am Am Setya (JBN (Jurnal Bedah Nasional), 2024)
Background : Iatrogenic bile duct injuries (BDI) are associated with fatal complications and increased mortality. Bile duct injuries can be caused by imprecise bile duct cutting, dislodged surgical clips, tearing or obstruction by fibrosis as a result of thermal injury by electrocautery resulting in biliary leakage and/or stricture. The aim of this study is to identify characteristics and predisposing factors of bile duct injury in our center. Methods : This study is a cohort retrospective study, with 42 cases of iatrogenic BDI following cholecystectomy (after both open and laparoscopic approaches); both happened in or were referred to Hasan Sadikin Hospital from September 2023 to September 2024. Patients were classified according to age, gender, BMI, Strasberg – Bismuth classification, laboratory values, and imaging findings. Results : In this study, there were 43 subjects, with majority of subjects aged ?40 years old (58%). There was no difference in gender, with 22 males and 21 females. The mean BMI was 26.1 ± 5.1 kg/m2. Majority of the cases were type E2 Strasberg – Bismuth classification (76.7%). This study found age ?40 years old (p value = 0.00), abnormal preoperative liver function (p value = 0.01), and gallbladder wall thickening (p value = 0.01) as significant predisposing factors of BDI. Conclusion: Age ?40 years old, abnormal preoperative liver function, and gallbladder wall thickening are significant predisposing factors of BDI. Data of anatomical variations and surgeon’s expertise should be beneficial for improvement of future studies.